2006
DOI: 10.2214/ajr.04.1520
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Conserving Surgery After Chemotherapy: Value of MDCT for Determining Tumor Distribution and Shrinkage Pattern

Abstract: MDCT classification of tumor distribution before neoadjuvant chemotherapy and of shrinkage patterns after neoadjuvant chemotherapy is important in the preoperative evaluation of patients undergoing breast-conserving surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 15 publications
1
37
1
Order By: Relevance
“…Findings of previous studies have demonstrated the usefulness of imaging modalities for determining the tumor distribution of residual breast carcinoma following NAC (7)(8)(9)(10)(11)(12). A study by Tozaki et al (9) analyzed computed tomography (CT) findings of tumor distribution patterns of locally-advanced breast carcinomas prior and subsequent to NAC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings of previous studies have demonstrated the usefulness of imaging modalities for determining the tumor distribution of residual breast carcinoma following NAC (7)(8)(9)(10)(11)(12). A study by Tozaki et al (9) analyzed computed tomography (CT) findings of tumor distribution patterns of locally-advanced breast carcinomas prior and subsequent to NAC.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Tozaki et al (9) analyzed computed tomography (CT) findings of tumor distribution patterns of locally-advanced breast carcinomas prior and subsequent to NAC. The distribution patterns of the enhancing lesions of breast carcinomas prior to NAC were classified into five categories: Solitary, grouped, separated, mixed and replaced lesions; and the shrinkage patterns subsequent to NAC were classified into three categories: Concentric shrinkage with or without surrounding lesions and shrinkage with residual multinodular lesions (9). The study concluded that CT classification of tumor distribution prior to NAC and shrinkage patterns subsequent to NAC is important for the evaluation of the residual lesions undergoing breast-conserving surgery (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI and CT have recently developed the potential to assist the other traditional imaging methods in the evaluation of response to NAC [12]- [20]. By mammography, it is difficult to identify a mass lesion in dense breasts or to distinguish a viable lesion from a fibrous reaction owing to NAC.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer can be classified into several patterns based on morphology (5,(15)(16)(17). In addition, the pattern of response to NAC depends largely on the initial morphology (15,16).…”
Section: Introductionmentioning
confidence: 99%